O sentido do trabalho pluriativo para os agricultores familiares: um estudo á partir da cooperativa de recicladores orgânicos e inorgânicos de santa cecília do sul/RS - Virgolin, Isadora Wayhs Cadore (2012)
The main point of this work is the pluriactivity in rural zone, specifically in family farms. This phenomenon consists of individuals from families living in the countryside were there to carry out one or more of the economic activities other than agriculture. Therefore, this research was conducted with a group of eleven family farmers that conciliate agricultural activity with the activity of recycling in Cooperative of recyclers of both organic and inorganic, situated in the rural zone of the Santa Cecilia do Sul city in the northeastern region of Rio Grande do Sul. The general objective of the study was to analyse the meaning of work for pluriativos family farmers from their binding to the cooperative. The research was characterised as qualitative. A bibliographic review was made of the main authors that discuss the dissertation in order to subsidize the main categories of research analysis. The empirical data were collected through semi-structured interviews. Data were systematized and analyzed through content analysis. The survey results showed that are significant transformations in the rural and that the pluriactivity can be pointed to as a strategy that families are using for ensuring their social reproduction. Moreover, it was found that the conciliation of farm work with another activity has engendered new meanings of work to the farmer. These meanings happen mainly by the process which gets with the socio-occupational identity of the pluriativos workers but there isn t rupture in the professional identification with the agriculture and the creation of a new identity added with other. Also it can be watched that the practice of pluriactivity went on to generate other senses that cut across the economic and financial aspect relating to family relations, sociability, social roles, the autonomy of workers, the social role of work activities, among others. At the same time, good points are raised, and the pluriactivity also results in a negative sense in light of work overload for the subject of this research.